2003
DOI: 10.1897/02-237
|View full text |Cite
|
Sign up to set email alerts
|

Changes in growth and secondary sex characteristics of fathead minnows exposed to bleached sulfite mill effluent

Abstract: Yellow perch captured downstream of a bleached sulfite mill had reduced gonad size and fecundity, and circulating steroid levels declined in goldfish exposed to final effluent for 21 d. To assess bleached sulfite mill (BSM) effluent, long-term fathead minnow (Pimephales promelas) growth and reproduction tests were carried out in a flow-through bioassay trailer at the mill secondary treatment lagoons. Fertilized P. promelas eggs were hatched in effluent (0, 1, 3.2, 10, 32, 50, and 100% final effluent with 10 ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 31 publications
2
32
1
Order By: Relevance
“…Hence, the cause for higher HSI means in fish exposed to the river waters was probably not limited to estrogenic active compounds. Increased HSI values related to EE2 exposure were also reported in other studies (Parrott et al, 2003;Versonnen et al, 2003).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Hence, the cause for higher HSI means in fish exposed to the river waters was probably not limited to estrogenic active compounds. Increased HSI values related to EE2 exposure were also reported in other studies (Parrott et al, 2003;Versonnen et al, 2003).…”
Section: Discussionsupporting
confidence: 84%
“…Induction of VTG in male fish has proven to be a sensitive endpoint for detection of estrogenic active EDCs as well as of effluents and surface waters (Kramer et al, 1998;Sheahan et al, 2002;Parrott et al, 2003;Jobling et al, 2004). VTG is an oestrogendependent yolk protein precursor synthesized in the liver and transported by the blood stream to the female gonads where it is incorporated in the developing oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, a more recent study opposed that claim, and suggested the disruption of estradiol metabolism by DHAA as an alternative explanation (Pandelides et al 2014). Occurrence of androgens in effluents from bleached kraft mill (Larsson et al 2006), and bleached sulphite mill (Parrott et al 2003), could explain the potential for competitive binding of ER by AR-agonists, or even non-ER-mediated signalling, i.e. AR-based response, in exposed fish.…”
Section: Industrial Sediment Ppm: Responses Of Estrogenic Biomarkersmentioning
confidence: 99%
“…fathead minnow, Pimephales promelas) that can be detected in a concentrationdependent manner by the very sensitive reactions of the fishes (Parrott & Wood 2002, Parrott et al 2003, Kovacs et al 2005. Genotoxic effects of wood dusts on DNA have recently been recorded in human lymphocytes in a test system referred to as Comet assay (Faust et al 2004).…”
Section: Bioindicators In Applications Of Wood Industrymentioning
confidence: 99%